Chromosome-level genome assemblies of Verpa bohemica and Verpa conica - Zhuyue Yan; Xiaofei Shi; Yingli Cai; Wenhua Sun; Peixin He; Liyuan Wu; Jin Zhang; Xing Guo; Bo Wang; Fuqiang Yu; Wei Liu (Scientific Data)
Abstract Verpa, commonly known as “early morel” or “false morel”, plays an important ecological role and offers considerable economic and medicinal potential. Despite their significance, research on Verpa species, particularly V. bohemica and V. conica, remains limited. In this study, we assembled high-quality sub-chromosomal genomes of six Verpa strains using Nanopore and Illumina sequencing, with average sizes of 44.38 Mb for V. bohemica and 45.40 Mb for V. conica. Specifically, the assemblies of V. bohemica strain 21108 and V. conica strain 21120 were anchored to 26 and 25 chromosomes with Hi-C technologies, respectively. The consensus quality value (QV) of both V. bohemica and V. conica exceeded 40. In addition, an average of 11,024 and 11,052 protein-coding genes were identified for V. bohemica and V. conica, respectively, with BUSCO completeness scores ranging from 98.71% to 99.24%. Overall, these reported genomes will provide valuable genomic resources for the evolution and ecological roles research of Verpa.